Organizational Climate and Civil Servant Performance: The Mediating Role of Work Engagement in Agricultural Agencies in West Java - Prawiranegara, Taqiya Puteri; Harding, Diana; Lestari Kadiyono, Anissa (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The agricultural sector plays a vital role in Indonesia’s food security and economy, yet it often faces challenges such as limited resources, budget efficiency policies, and suboptimal employee performance. Within agricultural institutions, human resources are critical for the success of strategic programs, making it essential to examine how organizational climate and work engagement influence employee performance. This study aims to analyze the effect of organizational climate on performance with work engagement as a mediator. Using a quantitative cross-sectional design, the research involved 75 civil servants in agricultural institutions in West Java through a total sampling technique. Data were collected using questionnaires measuring organizational climate (LSOCQ), work engagement (UWES), and job performance (IWPQ), and analyzed with regression and mediation testing via Hayes PROCESS Macro. The findings indicate that organizational climate positively and significantly influences work engagement, work engagement significantly affects performance, and fully mediates the relationship between organizational climate and performance. Thus, the positive effect of organizational climate on performance occurs indirectly through work engagement. These results support the Job Demands-Resources (JD-R) theory, positioning organizational climate as a crucial job resource that fosters vigor, dedication, and absorption, thereby enhancing employee performance. Practically, this study highlights the importance of creating a supportive organizational climate and strengthening work engagement strategies to improve productivity and food security in the agricultural sector.Sektor pertanian memiliki peran vital dalam ketahanan pangan dan perekonomian Indonesia, namun sering menghadapi tantangan berupa keterbatasan sumber daya, efisiensi anggaran, dan kinerja pegawai yang belum optimal. Dalam konteks instansi pertanian, kualitas sumber daya manusia menjadi salah satu aktor penentu keberhasilan program strategis, sehingga pemahaman mengenai peran iklim organisasi dan keterlibatan kerja terhadap kinerja pegawai pertaniaN enjadi penting. Penelitian ini bertujuan untuk menganalisis pengaruh iklim organisasi terhadap kinerja pegawai dengan keterlibatan kerja sebagai mediator. Menggunakan desain kuantitatif cross-sectional, penelitian melibatkan 75 Pegawai Negeri Sipil pada instansi pertanian di Jawa Barat dengan teknik total sampling. Data dikumpulkan melalui kuesioner yang mengukur iklim organisasi (LSOCQ), keterlibatan kerja (UWES), dan kinerja (IWPQ), lalu dianalisis menggunakan regresi dan uji mediasi Hayes PROCESS Macro. Hasil penelitian menunjukkan bahwa iklim organisasi berpengaruh positif signifikan terhadap keterlibatan kerja, keterlibatan kerja berpengaruh signifikan terhadap kinerja pegawai, serta keterlibatan kerja memediasi secara penuh hubungan iklim organisasi dan kinerja. Artinya, pengaruh positif iklim organisasi terhadap kinerja tidak langsung, melainkan melalui keterlibatan kerja. Temuan ini memperkuat teori Job Demands-Resources JD-R) yang menempatkan iklim organisasi sebagai job resource penting yang menumbuhkan vigor, dedication dan absorption sehingga meningkatkan kinerja pegawai. Secara praktis, hasil penelitian menekankan pentingnya menciptakan iklim organisasi yang kondusif dan strategi peningkatan keterlibatan kerja untuk mendukung produktivitas dan ketahanan pangan di sektor pertanian.